As primeiras décadas da eletricidade e do saneamento básico na capital paraibana , 1900-1940 - Nogueira, Helena de Cássia (2005)
This dissertation discusses the early decades (1900-1940) of the history of three public utilities provision of electricity, water supply and sewage disposal in the capital of the State of Paraíba, Brazil. Their introduction took place quite late in comparison with many Brazilian towns and cities (only in 1912 and 1924) and was preceded by some unsuccessful attempts. It was thanks to the determination of Governor João Machado that Parahyba do Norte, then small and backward, could have access to piped water and electricity, which ensures him an outstanding place in the modern history of the town. Assigned to an inefficient private company from São Paulo, electricity supply represented a problem until it became a State service, in 1933. Better results were achieved in the two other utilities, operated since the beginning by the State administration, as the best Brazilian expert in their field, Saturnino de Brito, conceived and executed both the extension of the water supply system and the sewerage system, assuring them modern and appropriate characteristics